Feasibility of Magnetic Technique for Axillary Staging after Neoadjuvant Therapy in Breast Cancer Patients. Issue 6 (1st June 2022) - Yılmaz, Osman Cem; Vural, Veli
Abstract: Purpose: Optimal axillary staging after neoadjuvant chemotherapy (NAC) in node-negative breast cancer is an area of controversy. Sentinel node biopsy with Technetium-sulphur colloid (99m Tc) alone or with blue dye is the recommended technique for evaluating axilla in these patients. However, this technique has drawbacks such as limited access to nuclear departments and timing limitations related to Tc injection exposing patients to unnecessary radiation. Superparamagnetic iron oxide nanoparticles (SPIO) may represent a valid option for SLN biopsy. In this study, we assessed the feasibility of the magnetic technique (Sentimag) with combination of isosulfan blue dye in breast cancer patients who received NAC. Methods: The study sample consisted of 54 female breast cancer patients who received NAC. Sentinel node localization was performed using magnetic technique and blue dye. Sentinel node identification rate (IFR) of magnetic technique was calculated and postoperative complications were assessed. Results: Sentinel lymph node was detected in 52 patients with Sentimag method (identification rate = 96.3%, 95% CI: 87.4–98.9%). Blue dye was successful to find SLN in 38 patients (identification rate = 70%). The most common histologic type was invasive ductal ( n = 51; 94.4%). Mean tumor size was 2.1 cm after NAC. Most of patients had T2 ( n = 30; 55.5%) and HER2 + positive ( n = 49; 90.7%) cancer. Conclusion: Sentimag which is a magnetic technique appears to be safe, easy to perform with minimal adverse effects, may be an alternative and accurate technique in patients with NAC, especially in breast units where nuclear medicine unit is not available. Supplemental data for this article is available online at https://doi.org/10.1080/08941939.2022.2038737 .